Role-Playing In English Language Training for Hotel Receptionists: A Systematic Review - Abdul Syahid; Refi Kamariah; Mayra Musdalifah; Putri Sulastri Permata Sari (Jurnal Kajian dan Penelitian Umum, 2024)
Hotel receptionists play a crucial role in creating a positive first impression on guests. Good English language skills are essential for receptionists to effectively communicate with guests from various countries. Role-playing is an effective training method to enhance the English language skills of hotel receptionists. This systematic review evaluates the effectiveness of role-playing in English language training for hotel receptionists. Twenty studies from Google Scholar and Scopus were analyzed to assess the impact of role-playing on various aspects of receptionists' English language skills, such as fluency, vocabulary, grammar, and confidence. The review findings indicate that role-playing has a significant positive effect on all the English language skills aspects studied.